Simulation Study on Friction and Wear Law of Brake Pad in High-Power Disc Brake. (14th July 2019) - Zhang, S.; Hao, Q.; Liu, Y.; Jin, L.; Ma, F.; Sha, Z.; Yang, D.
Abstract : For the serious and uneven wear of the brake pad in the high-power disc brake during braking, the dynamic variation of the brake disc and the brake pad interface variable is considered, the wear calculation model is established based on the friction and wear mechanism, and the wear depth and volume of the brake pad can be calculated by equations. A finite element model of the brake disc and the brake pad is established by DEFORM software which can analyze wear of the brake pad directly. The variation trend of wear during braking is studied, and influences of braking load and initial braking speed on the wear are analyzed. The results show that the amount of the wear increases rapidly in the early wear stage of braking, and it becomes slow in the later stage; the wear of the brake pad is serious at the friction inlet and outlet, and the middle area of the brake pad is lightly worn; heavy braking load and high initial braking speed can exacerbate the wear of the brake pad.